Palaeobotanical investigations of some peat deposits of Norse age at Qagssiarssuk, South Greenland. - Fredskild, Bent (Meddelelser om Grønland, 1978)
Pollen- and macrofossil diagrams have been worked out from transects in four peat-covered depressions between Norse ruins at Qagssiarssuk. Willow scrub, rich in ferns and herbs, covered the area at the time of the landnam. After a clearance, grass-sedge communities rich in weeds, especially annuals, covered the area. Towards the end of the Norse period some of the transects indicate moister local conditions. Later on willow scrub spread again in the area. The history of some "Norse plants" is discussed, and finally the influence of the first agriculture on the vegetation in S. Greenland is compared with similar events in Scandinavia, Faroe Islands and Iceland.